Update on MRI in pediatric intracranial germ cell tumors-The clinical and radiological features - Mingwen Yang; Jian Wang; Lin Zhang; Jungang Liu (Frontiers Media S.A., 2023)
Intracranial germ cell tumors (iGCTs) are uncommon brain tumors that mainly occur in children. Differing in histology, location, and gender of the patients, iGCTs are often divided into germinomas and non-germinomatous germ cell tumors (NGGCTs). Early diagnosis and timely treatment are crucial to iGCTs, the subtypes of which have substantial variations. This review summarized the clinical and radiological features of iGCTs at different sites, and reviewed the recent advances in neuroimaging of iGCTs, which can help predict tumor subtypes early and guide clinical decision-making.